Analysis of Initial Planning and Eco-friendly Tourism Development Strategy at Pantai Indah Kapuk 2 - Amellita, Nesya; Candra, Ahmad; Wiwik Dwi Pratiwi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The development of sustainable and eco-friendly tourism is crucial in the current global environmental crisis. The PIK 2 area in North Jakarta has the potential to become an eco friendly tourist destination, but proper planning and strategy are required. This research aims to analyze the initial planning and develop an eco-friendly tourism strategy in PIK 2. The research method consists of feasibility studies, field observations, and in-depth interviews. The analysis shows that PIK 2 has the potential to become a leading tourist destination, but challenges like infrastructure, community engagement, and environmental sustainability need to be addressed effectively. With the right strategy, PIK 2 can provide economic, social, and environmental benefits to local communities and visitors. Based on the analysis, an eco-friendly tourism development strategy was developed in PIK 2, which includes: 1) institutional strengthening; 2) sustainable development with ecological principles; 3) an education program on the importance of environmental conservation; 4) implementation of green development concepts in infrastructure and supporting facilities; 5) promotion and marketing of sustainable tourism; and 6) regular evaluation and monitoring. The implementation of this strategy is expected to realize PIK 2 as a competitive eco-friendly tourist destination and bring long-term benefits to the community and the surrounding environment.